Czechoslovak Army and Bicycle Units - Hubený, David; Kruglova, Nadezda (Before the Battle, 2023)
In the last three decades of the 19th century, the rising popularity of bicycles attracted the attention of army commanders. Soon, they noticed the striking advantages of using bicycles, including speeding up the infantry’s movements. Another great benefit was that bicycles did not require much attention, unlike the most renowned yet demanding form of transportation – horses, which necessitated the presence of special troops in the cavalry to take care of the animals. Therefore, cycling proved to be the cheapest form of personal transportation for the army at that time. Since its establishment, the Czechoslovak army has used bicycle units. Each border battalion had its own company of cyclists. In the early 1930s, there were several studies on bicycle units and shortly after that, four bicycle battalions joined the cavalry brigades. In 1937, a fifth bicycle battalion was formed. These units were considered to be the most well-trained, forming a valuable part of the fast divisions. In 1938, bicycle battalions were a part of the operation against the uprising of Heinlein’s terrorists; bicycle units also operated on the territory of Subcarpathian Rus, suppressing the activities of Polish and Hungarian sabotage groups. The article discusses the history of the development of the Czechoslovakian bicycle units and scrutinises how the Czechoslovak military perceived this phenomenon. The paper also includes information about foreign bicycle units.